The Right Backpack: Guidelines for Parents - Suzanna Smith (EDIS)
FCS-2246, a 3-page illustrated fact sheet by Suzanna Smith, provides guidelines to parents for using backpacks safely and preventing injuries. Describes signs of backpack-related injury and provides references. Published by the UF Department of Family Youth and Community Sciences, August 2006.